O tecnobrega no Pará: um estudo de caso a partir da banda Djavú & DJ Juninho Portugal (2008-2011) - GOMES, Max Aládio dos Santos (2023)
The present work seeks to show how the success of the Bahian tecnobrega band (Djavu & DJ Juninho Portugal), during the years 2008 to 2011, was seen within the territory of Pará, especially with regard to speeches by the local press and by tecnobrega artists of the region and, likewise, how the emergence of the band provided a process of valuing tecnobrega in Pará. For that, we searched in printed newspapers, internet sites, blog and YouTube, information that dealt with the band Djavu in its “conflict” with the paraense music scene. Methodologically, the speeches of these sources were treated in the light of Cultural History, as well as from a critical position regarding oral reports, given that the point of confluence of the aforementioned sources revolves around orality. In addition, theoretically, the concept of “Hybrid Cultures” was worked on, which served as a guide to situate tecnobrega as a product in a constant process of hybridization, so that it would become clear that its definition as an “original” product would be wrong, but it would not mean something negative.